2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627661
|View full text |Cite
|
Sign up to set email alerts
|

From pain to stress evaluation using Heart Rate Variability analysis: Development of an evaluation platform

Abstract: Heart Rate Variability analysis has been shown in several studies to measure the Autonomic Nervous System tone, which is strongly influenced by pain, stress or anxiety. We have previously described and developed an Analgesia/Nociception Index for pain measurement during surgical procedure. This index based on a heart rate variability analysis can be considered as a vagal tone index and used in several other environments. In this paper, we present an adaptation of our technology for stress / anxiety evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…11 Therefore, preliminary results obtained with the ANI monitor during orthopedic surgery under general anesthesia are promising, and have demonstrated that ANI can detect nociceptive states in conscious patients after surgery. 21 Further clinical investigations are in progress in conscious and anaesthetized patients during nociceptive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…11 Therefore, preliminary results obtained with the ANI monitor during orthopedic surgery under general anesthesia are promising, and have demonstrated that ANI can detect nociceptive states in conscious patients after surgery. 21 Further clinical investigations are in progress in conscious and anaesthetized patients during nociceptive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review shows that Internet-based programs appear to relieve pain [33]. Autonomic reactions refer to pain, stress, and anxiety [60]. A program of interactive online learning may reduce autonomic reactions by increasing knowledge about self-care techniques, thereby reducing pain and anxiety [34, 57] and stress [57, 61].…”
Section: Discussionmentioning
confidence: 99%
“…We just can claim that the protocol can describe with satisfactory accuracy the performance vs stress for a context of work. Nevertheless, it remains much less accurate than what could give the complex protocols including analysis of the whole set of physiological parameters (Fairclough et al, 2004;Montano et al, 2009;Müller et al, 2009;Rohleder et al, 2009;Schubert et al 2009;Bailon et al, 2010;De Jonckheere et al, 2010;Jo et al, 2013). Yet it gives a instant assessment of performance versus stress with a satisfactory accurateness for training centers.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary of sophisticated metrologies and elaborated software which need, thereafter, a careful data examination to be sure of the conclusions (Montano et al, 2009;Rohleder et al, 2009;Schubert et al 2009;Bailon et al, 2010;De Jonckheere et al, 2010;Jo et al, 2013), we aimed at a simple solution based on heart rate.…”
Section: Physiological Measurements During Trainingmentioning
confidence: 99%